Urinary cytokine and chemokine profiles across the menstrual cycle in healthy reproductive age women - Whitcomb, Brian W. (2014)
OBJECTIVE: To assess utility of urinary cytokines for monitoring reproductive function by considering detection, variation across the menstrual cycle, and relations with hormones. DESIGN: Longitudinal cohort study SETTING: Academic institution. PARTICIPANTS: Healthy, reproductive aged women with self-reported regular menstrual cycles and at least one observed ovulatory cycle (n=248). INTERVENTION: None MAIN OUTCOME MEASURE: Urinary cytokines measured by 30-plex immunoassays in 3550 biospecimens. Nested random-effects ANOVA and marginal structural models used to evaluate variability and relations with hormones. RESULTS: For 24 of 30 evaluated factors, detectable levels were observed in at least 50% of urine samples. Interleukin (IL)-6, IL-8, IL-10, IL-15, granulocyte colony stimulating factor (G-CSF), hepatocyte growth factor (HGF), interferon (IFN)-α, and RANTES levels varied significantly across the menstrual cycle. The pro-inflammatory factors IL-1β, IL-6, IL-8, and HGF were 1.5 to 3 times higher during menses than the late follicular phase. In marginal structural models, IL-1β, IL-6, IL-8 were associated with lower estradiol and progesterone. CONCLUSIONS: Variability during the menstrual cycle and correlations with reproductive hormone levels support a role of cytokines in the menstrual cycle; however, because of the limited variability for most cytokines considered, the utility of urine as a matrix for assessment of inflammation in menstrual cycle function appears limited for clinical purposes.